1995
DOI: 10.1523/jneurosci.15-03-01961.1995
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin-1 in immobilization stress-induced increase in plasma adrenocorticotropic hormone and in release of hypothalamic monoamines in the rat

Abstract: We investigated whether interleukin-1 (IL-1) activity in the rat hypothalamus was increased by immobilization stress (IS), and whether pretreatment with an interleukin-1 receptor antagonist (IL-1Ra) is capable of inhibiting IS-induced elevations of hypothalamic norepinephrine (NE), dopamine (DA), and serotonin (5-HT) and the levels of their metabolites as well as of plasma adrenocorticotropic hormone (ACTH). IL-1 activity was estimated with a bioassay using mouse thymocyte proliferation in the presence of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
104
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(110 citation statements)
references
References 39 publications
6
104
0
Order By: Relevance
“…Most likely, glucocorticoid-independent mechanisms of thymic atrophy (Krenger et al, 2000) are related to catecholamine action (see Madden, 2003 for a comprehensive review of catecholamine effects on immune function). The effects of catecholamines on thymus weight and lifespan may be mediated by glucocorticoids in that NE production can stimulate interleukin-1 in turn stimulating the HPA axis (Shintani et al, 1995). Further work will have to include measures of personality-linked variance in catecholamines to better understand mechanisms underlying a relationship between personality, immune function and cancer susceptibility/progression (Elenkov & Chrousos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, glucocorticoid-independent mechanisms of thymic atrophy (Krenger et al, 2000) are related to catecholamine action (see Madden, 2003 for a comprehensive review of catecholamine effects on immune function). The effects of catecholamines on thymus weight and lifespan may be mediated by glucocorticoids in that NE production can stimulate interleukin-1 in turn stimulating the HPA axis (Shintani et al, 1995). Further work will have to include measures of personality-linked variance in catecholamines to better understand mechanisms underlying a relationship between personality, immune function and cancer susceptibility/progression (Elenkov & Chrousos, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Dunn (1993) revealed that intraperitoneal injection of IL-1/3 into mice accelerated NA turnover in cerebral cortex, hypothalamus, and brainstem and 5-HT turnover in cerebral cortex and brainstem. Shintani et al (1995) reported that immobilization stress in rats induced elevation of steady-state levels of hypothalamic NA, DA, and 5-HT through the enhanced production of IL-1~3in the brain. Although the effect of IL-1,@ on NAergic and serotonergic neurons observed in rats is consistent with the change in cachectic mice in the present study, the decrease in DAergic neuron activity in cachectic mice could not be induced by IL-1/3 (Dunn, 1993;Shintani et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Shintani et al (1995) reported that immobilization stress in rats induced elevation of steady-state levels of hypothalamic NA, DA, and 5-HT through the enhanced production of IL-1~3in the brain. Although the effect of IL-1,@ on NAergic and serotonergic neurons observed in rats is consistent with the change in cachectic mice in the present study, the decrease in DAergic neuron activity in cachectic mice could not be induced by IL-1/3 (Dunn, 1993;Shintani et al, 1995). Furthermore, Zalcman et al (1994) reported that intraperitoneal injection of IL-6 into mice accelerated DA and S-HT activities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to elevating serotonin levels, intrahippocampal IL-1 also increases HPA axis activity as evidenced by increases in plasma ACTH and corticosterone levels (Linthorst et al 1994). Immobilization stress elevates plasma ACTH and monoamines including serotonin within the hypothalamus, an effect which can be blocked by the use of an IL-1 receptor antagonist (Shintani et al 1995). Hence evidence exists suggesting that serotonin could play a role in mediating the effects of IL-1 , or LPS on the HPA axis.…”
Section: Introductionmentioning
confidence: 99%